2019
DOI: 10.1080/0284186x.2019.1643915
|View full text |Cite
|
Sign up to set email alerts
|

Preventive drug therapy and contralateral breast cancer: summary of the evidence of clinical trials and observational studies

Abstract: Background: Breast cancer patients have a lifelong 2-4-fold increased risk of developing a second primary tumor in the contralateral breast compared with the risk for a first primary breast cancer in the general female population. Prevention of contralateral breast cancer (CBC) has received increased attention during recent decades. Here, we summarize and discuss the available literature on drug preventive therapy and CBC. Results: The endocrine-targetting drugs, tamoxifen and aromatase inhibitors are used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…It is important to highlight that endocrine agents are also used in the breast cancer prevention setting. High quality evidence from observational studies and clinical trials has shown a reduced rate of breast cancer development in women at high‐risk by 40%–53% and a continued significant effect in the posttreatment follow‐up period 87–94 . However, utilization of preventive therapy remains poor mainly due to lack of physician and patient awareness, concerns about side effects (i.e., nausea, vomiting, hot flushes, musculoskeletal discomfort, fatigue and headaches for AIs, or vaginal bleeding, endometrial cancer and thromboembolism for tamoxifen) as well as other issues related to the need to improve our risk prediction models and develop surrogate biomarkers of response.…”
Section: Obesity and Endocrine Response In Breast Cancer: Epidemiolog...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight that endocrine agents are also used in the breast cancer prevention setting. High quality evidence from observational studies and clinical trials has shown a reduced rate of breast cancer development in women at high‐risk by 40%–53% and a continued significant effect in the posttreatment follow‐up period 87–94 . However, utilization of preventive therapy remains poor mainly due to lack of physician and patient awareness, concerns about side effects (i.e., nausea, vomiting, hot flushes, musculoskeletal discomfort, fatigue and headaches for AIs, or vaginal bleeding, endometrial cancer and thromboembolism for tamoxifen) as well as other issues related to the need to improve our risk prediction models and develop surrogate biomarkers of response.…”
Section: Obesity and Endocrine Response In Breast Cancer: Epidemiolog...mentioning
confidence: 99%
“…High quality evidence from observational studies and clinical trials has shown a reduced rate of breast cancer development in women at high‐risk by 40%–53% and a continued significant effect in the posttreatment follow‐up period. 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 However, utilization of preventive therapy remains poor mainly due to lack of physician and patient awareness, concerns about side effects (i.e., nausea, vomiting, hot flushes, musculoskeletal discomfort, fatigue and headaches for AIs, or vaginal bleeding, endometrial cancer and thromboembolism for tamoxifen) as well as other issues related to the need to improve our risk prediction models and develop surrogate biomarkers of response. For instance, evaluation of anthropometric parameters to identify women at high‐risk with greater accuracy and/or to predict sensitivity to breast cancer prevention are awaited with interest.…”
Section: Obesity and Endocrine Response In Breast Cancer: Epidemiolog...mentioning
confidence: 99%
“…Owing to the increasing morbidity of BC, prolongation of survival time and improvement of detection rate, a growing number of patients with BC are diagnosed as contralateral disease (2,3). Recently, majority of studies focused on risk factors for the formation of contralateral breast cancer (CBC) in patients with primary breast cancer (PBC) (4,(35)(36)(37)(38)(39)(40)(41)(42), and expected to prevent the occurrence of CBC via bilateral mastectomy (5,6). While for clinical practice, it is not yet clear whether patients would benefit from bilateral mastectomy in terms of mortality (5).…”
Section: Introductionmentioning
confidence: 99%